Ecological Validation and Reliability of Hexoskin Wearable Body Metrics Tool in Measuring Pre-exercise and Peak Heart Rate During Shuttle Run Test in Professional Handball Players - Haddad, Monoem; Hermassi, Souhail; Aganovic, Zlatan; Dalansi, Feriel; Kharbach, Mariam; Mohamed, Azam Omar; Bibi, Khalid W. (Frontiers in Physiology, 2020)
The aim of the study was to assess the validity and reliability of wearable body metric Hexoskin “smart shirt” in measuring heart rate (HR) at pre-exercise and during peak effort in a field test incorporating vigorous movements of the upper body. Measurements were recorded simultaneously using the Hexoskin and Polar Team Pro. Nine male professional handball players (age: 21.8 ± 2.4 years; weight: 83 ± 10.26 kg; height: 1.81 ± 0.09 m; BMI: 25.17 ± 2.23) volitionally participated in the study by completing two 400 m shuttle run test trials (10 shuttles), each separated by a 48h to 72h recovery period. Results indicated significant correlations between Hexoskin and Polar Team Pro system in pre-exercise HR. Hexoskin provided erroneous measurements in four of the nine athletes during peak effort. Subsequent correction yielded no consistency between the Polar Team Pro system and Hexoskin between the first and the second trial. Hexoskin showed significant reliability in pre-exercise HR. However, Hexoskin picked up excessive artifact during vigorous physical activity in four of the nine athletes rendering the results in these cases useless. Nevertheless, in athletes where artifact was not an issue, ICC yielded a good estimate. The main findings indicate that Hexoskin has good validity and reliability in measuring pre-exercise HR in handball players and hence may be used with high confidence in slow motion activities. However, vigorous physical activity with jarring multidirectional upper body movements posed a challenge for Hexoskin.